2011
DOI: 10.1007/978-3-642-19997-4_15
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Method for Engineering Social Web Services

Abstract: Abstract. This paper motivates the blend of social computing with service-oriented computing, giving "birth" to social Web services. On the one hand, social computing builds user applications upon the principles of collective action and content sharing. On the other hand, serviceoriented computing builds enterprise applications upon the principles of service offer and demand and loose coupling. Thanks to this blend social Web services can operate taking into account with whom they worked in the past and with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Different approaches that study social networks of Web services are reported in the literature. In [14] Maamar et al introduce a method for engineering social Web services. This engineering requires identifying relationships between Web services, mapping these relationships onto social networks, building social networks of social Web services, and setting the social behaviors of social Web services.…”
Section: When Social Computing Meets Service Computingmentioning
confidence: 99%
“…Different approaches that study social networks of Web services are reported in the literature. In [14] Maamar et al introduce a method for engineering social Web services. This engineering requires identifying relationships between Web services, mapping these relationships onto social networks, building social networks of social Web services, and setting the social behaviors of social Web services.…”
Section: When Social Computing Meets Service Computingmentioning
confidence: 99%
“…For example, a selfish WS continuously receives positive responses from peers when it seeks their assistance for substitution, but it does continuously the opposite, i.e., declines others' assistance requests [5].…”
Section: Definition (Selfishness)mentioning
confidence: 99%
“…However, several constraints continue to limit WSs adoption by the IT community, for instance WSs only know about themselves, not about their users' social connections or peers, they cannot also delegate their invocations to others peers, limit user's intervention considerably, and operate as black boxes [5]. Social computing seems offering innovative solutions to some of these limitations, which improves the quality of recommendations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the category of social networks of Web services, we cite our research works in [4] and [7]. In the first work, we suggest a method to engineer "social Web services".…”
Section: Literature Reviewmentioning
confidence: 99%